The possibility of applying of acoustic methods for the monitoring of sol-gel processes - RZESZOTARSKA, J.; RANACHOWSKI, J. (Archives of Acoustics, 2000)
Models simulating the propagation of acoustic waves in the successive stages of the gelation process are presented. The early stage of gelation has been considered with scattering theory for very low concentrations of suspensions. The system may be simulated by the line of the independent Maxwell elements. When concentration of the suspension increases, the interaction of the particles can be presented by an acoustic model, which consist of a chain of coupled Maxwell elements. After the gelation point, the system becomes rigid, and three dimensional tensoral fields distribution of stress and strain was used.